2020
DOI: 10.1186/s12939-020-1148-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of self-treatment behaviour among different elder subgroups in rural China: a cross-sectional study

Abstract: Background: Self-treatment is a common and widespread behaviour, of which the risks are multiplied in old age. However, the determinants of self-treatment among elders in rural China remain unclear. This study aims to explore the prevalence and associated factors of self-treatment among elders in rural China, trying to discover the vulnerable groups as well as the service gaps among the rural elders. Methods: Based on a multi-stage stratified random sampling method, a cross-sectional household survey was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…First, socioeconomic development and geographic distribution and suggestions from experts were assessed. Two counties (DY, Dangyang in Central China; SN, Sinan in Western China) were purposively selected [35]. Second, a multistage stratified random household survey was conducted with face-to-face interviews.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…First, socioeconomic development and geographic distribution and suggestions from experts were assessed. Two counties (DY, Dangyang in Central China; SN, Sinan in Western China) were purposively selected [35]. Second, a multistage stratified random household survey was conducted with face-to-face interviews.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…Global research shows that the rate of self-treatment, irrespective of whether developed or developing countries, is high. For example, the rate of self-treatment is 50.0% in India [ 8 ], 50.2% in Ethiopia [ 9 ], or 35.2% in rural China [ 6 ]. In the United States, 1%-66% of residents used antibiotics without prescription [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still major disparities in health conditions, health care service access, and use between residents living in remote/rural and urban areas in both developed and developing countries [2][3][4]. Geographical distance, constrained financial resources, and insufficient health services provided by qualified health professionals are the main barriers for people in remote areas to access health care, which may also increase the risk of selftreatment and self-medication in this population [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A study indicated that more than 4.2 million poor patients with serious or chronic diseases have been treated due to the health poverty alleviation project [26]. Another important explanation for non-empty nesters having a higher prevalence of self-treatment than empty ones is that the family caregivers are often equipped with some knowledge and common skills of healthcare tasks due to the increased frailty of the elderly, and the non-empty nesters would usually deal with their discomfort with the support of their adult children [20].The results suggests that it is important to strengthen health education for elderly and family caregivers to make them understand the risks of improper self-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the potential determinates of self-treatment among the elderly. The decision to choose self-treatment involves a complex mechanism and is influenced by various factors, including individual, household, accessibility and medical insurance system factors [10,20]. Few studies, however, exist to date in China focusing on the roles of social changes and living arrangements in the use of self-treatment.…”
Section: Introductionmentioning
confidence: 99%